Essays on “Matching” in experimental economics - Zhao, Zichen (Nanyang Technological University, 2023)
This thesis comprises three chapters studying the concepts of “matching” in experimental economics. Chapter 1 studies the topic of matching and cooperation in teams consisting of heterogeneous individuals with multiple task options. Specifically, chapter 1 analyzes the effects of leadership by endogenous task choice on cooperation in teams of individuals with heterogeneous abilities across task options. Our experiment shows that contributions increase when tasks are initiated by a leader instead of exogenously by Nature, and in stable teams. Leaders cooperate more, even in costlier tasks, as do followers. The observed task choices elicit more efficiency especially in repeated games; participants alternate between tasks when it also achieves equity across games. These results indicate the engagement effects of endogenously chosen tasks and stable partnerships that transform social preferences. We theoretically discuss this with examples such as on how leaders are more willing to accept disadvantageous inequity and more likely to pick efficient and equitable tasks and trust or reciprocate, while followers respond to leadership with reciprocity or trust, respectively. Chapter 2 studies the design of incentives to elicit optimal matching of heterogeneous individuals endogenously. Specifically, chapter 2 investigates the role of incentives in determining how individuals with high or low ability endogenously match to form teams. We show that standard incentives that reward the best performing team (team incentives) or the best performing member of each team (individual incentives) always lead to the formation of homogeneous teams even when socially inefficient. We then propose hybrid incentives that combine team and individual incentives to motivate individuals to form homogeneous or heterogeneous teams that are always optimal, and experimentally evaluate its feasibility. The experiments show that matching behaviors are consistent with model predictions under self-interest. Hybrid incentives are possible to always incentivize the socially optimal matching of abilities. Participants make equilibrium proposals more frequently in our hybrid scheme when provided with information on the expected value of respective matches. Chapter 3 studies concept of matching from a methodological perspective by verifying whether the stated claims match with the experimental data in economic papers. Chapter 3 presents a study comparing claims based on laboratory and field experiments in 520 publications in 2018 and 2019 at leading general and field journals in economics. Each paper is surveyed for their key claims and matches along the dimensions of profession, age, and gender of experimental subjects; country of experiment; and experimental asset. We define a match for a given dimension if there is a correspondence between the specific experiment being conducted and the claims made for that dimension. We find that, particularly in the realm of policy testbed, field experiments are more likely to match the claims than laboratory experiments. However, depending on the dimension, less than 20% or only up to around 65% of field experiments, including natural field experiments, achieve a match. Around four out of five field experiments fail to match in at least three out of five of the dimensions considered. Natural field experiments do not have a systematically higher match than the other types of field experiments. We conclude that the methodological challenge of generalizing results beyond what is within the domain of the experiments themselves also applies to many papers based on field experiments, given the claims being made.